Comprehensive Analysis of 5-Aminolevulinic Acid Dehydrogenase (ALAD) Variants and Renal Cell Carcinoma Risk among Individuals Exposed to Lead - van Bemmel, Dana M.; Boffetta, Paolo; Liao, Linda M.; Berndt, Sonja I.; Menashe, Idan; Yeager, Meredith; Chanock, Stephen; Karami, Sara; Zaridze, David; Matteev, Vsevolod; Janout, Vladimir; Kollarova, Hellena; et al. (PloS one, 2011)
Epidemiologic studies are reporting associations between lead exposure and human cancers. A polymorphism in the 5-aminolevulinic acid dehydratase (ALAD) gene affects lead toxicokinetics and may modify the adverse effects of lead. The objective of this study was to evaluate single-nucleotide polymorphisms (SNPs) tagging the ALAD region among renal cancer cases and controls to determine whether genetic variation alters the relationship between lead and renal cancer. Occupational exposure to lead and risk of cancer was examined in a case-control study of renal cell carcinoma (RCC). Comprehensive analysis of variation across the ALAD gene was assessed using a tagging SNP approach among 987 cases and 1298 controls. Occupational lead exposure was estimated using questionnaire-based exposure assessment and expert review. Odds ratios (OR) and 95% confidence intervals (CI) were calculated using logistic regression. The adjusted risk associated with the ALAD variant rs8177796(CT/TT) was increased (OR = 1.35, 95%CI = 1.05-1.73, p-value = 0.02) when compared to the major allele, regardless of lead exposure. Joint effects of lead and ALAD rs2761016 suggest an increased RCC risk for the homozygous wild-type and heterozygous alleles ((GG)OR = 2.68, 95%CI = 1.17-6.12, p = 0.01; (GA)OR = 1.79, 95%CI = 1.06-3.04 with an interaction approaching significance (p(int) = 0.06). No significant modification in RCC risk was observed for the functional variant rs1800435(K68N). Haplotype analysis identified a region associated with risk supporting tagging SNP results. A common genetic variation in ALAD may alter the risk of RCC overall, and among individuals occupationally exposed to lead. Further work in larger exposed populations is warranted to determine if ALAD modifies RCC risk associated with lead exposure.